Heat resistive, binder‐free 3d‐dough composite as a highly potent flame‐retardant. Issue 20 (6th January 2022) - Dhumal, Pratik S.; Lokhande, Kshama D.; Bondarde, Mahesh P.; Bhakare, Madhuri A.; Some, Surajit
Abstract: We have synthesized sodium polyacrylate and bentonite supported phosphorous functionalized flame retardant (FR) dough material. The dough material has flame retardant and heat insulator properties. The combination of sodium polyacrylate and bentonite provided strength and flexibility, whereas the phosphorus functionalities contributed the flame retardant property to the FR‐dough. The major benefit of the FR‐dough composite is that it can be simply converted into any 3D shape without the use of any binder and can be easily connected to any surface area without the use of any adhesives. The FR‐dough was successfully applied on the wood stick and electric wire for the flame‐retardant test. These coated materials were sustained on the flame for more than 120 s without any damage, while the only sample burnt out within the 40 s. The flame retardancy and heat resistance properties of the material have been confirmed by conducting a Bunsen burner test as the burner can attain a temperature up to 1500°C. The composite also has smoke absorption and self‐healing properties along with flame retardant and heat resistive properties. This approach has a high potential in the mass production of this multifunctional FR‐dough composite. Abstract : In this research, a FR‐dough composite was designed that can be easily molded into various 3d‐shapes without the use of a binder. The composite was investigated as a heat resistant and flame retardant material. Without using any adhesives, the composite was applied to a various of surfaces. The Bunsen burner flame (1500°C) was easily protected by this composite for more than 5 minutes. After the flame experiments, the FR‐dough was easily recycled.